PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE TPS UNTUK MENINGKATKAN HASIL BELAJAR MATEMATIKA DI SD NEGERI 6 BUKIT BATU KECAMATAN BUKIT BATU - Yusmanidar Yusmanidar (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Riau, 2018)
This research is motivated by the problem of low learning outcomes of students on learning mathematics in SDNegeri 6 Bukit Batu Bukit Batu Subdistrict. Students are not accustomed to dare to ask questions or expressopinions during learning activities, this happens because the learning atmosphere often makes students feel bored.Therefore, the teacher tried to use cooperative learning model of TPS type as a learning media in order to create aninteresting and fun learning atmosphere. the purpose of this study is to improve the learning process and improvethe learning outcomes of fourth grade students of SD Negeri 6 Bukit Batu in the academic year 2017/2018, throughthe implementation of cooperative learning model of TPS. The study was conducted in two cycles, one cycle wasconducted twice as much research. The subjects of the study were class of students of class IV as many as 26 peopleconsisting of 15 male students and 11 female students, conducted on the even semester of 2017/2018 academic yearin April 2018. Technique of collecting data, among others, with observation sheet and test sheet during the actionand documentation of learning activities. The result of learning cycle 1 obtained an average of 74.28 and cycle 2with an average of 85.20 in Mathematics lesson can be concluded, that the model of cooperative learning TPS typecan improve the learning outcomes of students of grade IV of SD Negeri 6 Bukit Batu. This is evident from theaverage increase in student learning outcomes of 85, 20 significant increases in cycle II. This success is supportedby the readiness of teachers in designing learning and learning process that is implemented according to plan